Optimising magnetocuring parameters for testing adhesion strength of magnetocuring epoxy resins - Ong, Sheng Jian (Nanyang Technological University, 2023)
Magnetocuring is a novel adhesive activation method that allows contactless crosslinking initiation via an alternating magnetic field. Magnetocuring can help to save energy, time, and formulation by curing the adhesive quickly from a localized heating zone. In this study, BDDE was chosen as the model epoxy system to study frontal polymerization. Curing kinetics and morphologies of cured products show variations when CNP concentrations and thermal initiator type (TBPB, BPO) are changed. During this study, specific absorption value (SAR), shear properties, and magneto-rheological properties were measured. This study can help in predicting magentocuring behaviours and formulations of BDDE epoxy in the future.